Evidence of an Inverted U–Shaped Relationship between Stakeholder Management Performance Variation and Firm Performance - Laplume, André O.; Harrison, Jeffrey S.; Zhang, Zhou; Yu, Xin; Walker, Kent (Business ethics quarterly, 2022)
Empirical research is largely supportive of the assertion of instrumental stakeholder theory that a positive relationship exists between “managing for stakeholders” and firm performance. However, despite considerable debate on the subject, the amount of variation across firm investments in stakeholders (stakeholder management performance) has not been adequately investigated. We address this gap using a sample of more than eighteen thousand firm-level observations over ten years. We find evidence to support an inverted U–shaped relationship between variation in stakeholder management performance and Tobin’s q, suggesting that firms that have some imbalance in their stakeholder management, but not too much, perform best. We discuss the implications of our study for instrumental stakeholder theory and managerial practice.